2012
DOI: 10.1021/jp302531d
|View full text |Cite
|
Sign up to set email alerts
|

Thermal Conductivity of Ordered Mesoporous Nanocrystalline Silicon Thin Films Made from Magnesium Reduction of Polymer-Templated Silica

Abstract: This paper reports the cross-plane thermal conductivity of ordered mesoporous nanocrystalline silicon thin films between 25 and 315 K. The films were produced by evaporation-induced self-assembly of mesoporous silica followed by magnesium reduction. The periodic ordering of pores in mesoporous silicon was characterized by X-ray diffraction and direct SEM imaging. The average crystallite size, porosity, and film thickness were about 13 nm, 25−35%, and 140−340 nm, respectively. The pores were arranged in a face-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
18
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 35 publications
(19 citation statements)
references
References 44 publications
1
18
0
Order By: Relevance
“…11 We can take advantage of the phonon scattering on boundaries to reduce the thermal conductivity for high performance of thermoelectric devices. Existing studies [12][13][14][15][16][17] suggested that nano-porous thin films can block heat transfer easily, and result in thin films with low thermal conductivity. However, the experimental study is often constrained by the nanofabrication due to the nanoscale, and high measurement accuracy of experimental system is often difficult to achieve and the cost is expensive as well.…”
Section: Introductionmentioning
confidence: 99%
“…11 We can take advantage of the phonon scattering on boundaries to reduce the thermal conductivity for high performance of thermoelectric devices. Existing studies [12][13][14][15][16][17] suggested that nano-porous thin films can block heat transfer easily, and result in thin films with low thermal conductivity. However, the experimental study is often constrained by the nanofabrication due to the nanoscale, and high measurement accuracy of experimental system is often difficult to achieve and the cost is expensive as well.…”
Section: Introductionmentioning
confidence: 99%
“…To avoid the effect of the substrate upon experimental accuracy, self-standing PSi membranes have been used as specimens (Maccagnani et al ., 1999;Song and Chen, 2004;Bernini et al , 2005). Theoretical analyses have also been conducted on the basis of molecular dynamics simulations , nanodot array fabrication (Fang et al ., 2012), and the hydrodynamic approach (Alvarez et al ., 2010).…”
Section: Experimental Datamentioning
confidence: 99%
“…The experimental results on pSi show that its thermal conductivity is strongly related to the pore size at a given total porosity [37][38][39]110]. Since an increasing porosity may deteriorate the electron transport properties [5,75], it would be advantageous if its effective thermal conductivity could be controlled by the volume fractions, as well as the characteristic size of the pores.…”
Section: Pore-size Dependence Of the Effective Thermal Conductivity Imentioning
confidence: 99%